Anti-Interleukin 5 (IL-5) and IL-5Ra Biological Drugs: Efficacy, Safety, and Future Perspectives in Severe Eosinophilic Asthma - Bagnasco, Diego; Ferrando, Matteo; Varricchi, Gilda; Puggioni, Francesca; Passalacqua, Giovanni; Canonica, Giorgio Walter (Frontiers in Medicine, 2017)
The definition of asthma has changed considerably in recent years, to the extent that asthma is no longer considered a single disease but a heterogeneous disorder that includes several phenotypes and, possibly, endotypes. A more detailed analysis of the immunological mechanisms underlying the pathogenesis of asthma shows interleukin 5 (IL-5) to be a crucial cytokine in several asthma phenotypes. In fact, IL-5 exerts selective action on eosinophils, which, in turn, sustain airway inflammation and worsen asthma symptoms and control. Clinical trials have shown drugs targeting IL-5 or its receptor alpha subunit (IL-5Ra) to be a promising therapeutic approach to severe asthma, whose characteristics render standard therapy of little use: systemic corticosteroids only partially control the disease and have well-known adverse effects, and omalizumab is used for allergic subtypes. Analysis of the design process of clinical trials reveals the importance of patient selection, taking into account both clinical data (e.g., exacerbations, lung function, and quality of life) and biomarkers (e.g., eosinophils, which are predictive of therapeutic response).